Efficient and eco-friendly treatment of wastewater through sustainable purification using agricultural waste and coagulation kinetic modelling - Varsani, Vaishali G.; Vyas, Suhas J.; Parmar, Vijay; Dudhagara, Dushyant; Gamit, Sandip; Ali, Daoud; Yadav, Virendra Kumar; Sahoo, Dipak Kumar; Patel, Ashish (Frontiers in Environmental Science, 2024)
This scientific manuscript presents a comprehensive investigation into the purification of municipal sewage water through the utilization of agricultural waste materials [Arachis hypogaea shells (AHS), Triticum aestivum straw (TAS), and Gossypium herbaceum shells (GHS)].The treatment process involved a modified approach with 24hrs of aeration and the addition of 1 gm of agricultural waste biomaterials. The performance of the bio-coagulant was evaluated by monitoring the reduction of physico-chemical parameters. AHS exhibited remarkable turbidity removal efficiency of 93.37%, supported by pseudo-first and pseudo-second-order kinetic modelling. The application of agricultural waste materials significantly reduced key parameters, including solids (up to 70-80%), dissolved oxygen (DO) (50%), biological oxygen demand (BOD) and chemical oxygen demand (COD) (up to 90%). Principal Component Analysis (PCA) showed the significant positive loading of PC1 (84.71%) that influencing the dual treatments of wastewater. Statistical analysis (P<0.05) confirmed the effectiveness of agricultural biomaterials in sewage water treatment compared to pre-treated water. The turbidity coagulation pseudo-first-order and pseudo-second-order kinetic modelling also revealed the efficiency against turbidity reduction in municipal sewage water. The findings underscore the significance of utilizing agricultural waste materials for sustainable and efficient purification of municipal sewage water, addressing water pollution and enhancing wastewater treatment processes.